Теоретическое моделирование упорядочения меди в CuAl сплавах - Инербаев, Т.; Кавазое, Ё. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Theoretical modeling of copper ordering in CuAl alloys